2012
DOI: 10.1371/journal.pone.0033900
|View full text |Cite
|
Sign up to set email alerts
|

Additive Pressures of Elevated Sea Surface Temperatures and Herbicides on Symbiont-Bearing Foraminifera

Abstract: Elevated ocean temperatures and agrochemical pollution individually threaten inshore coral reefs, but these pressures are likely to occur simultaneously. Experiments were conducted to evaluate the combined effects of elevated temperature and the photosystem II (PSII) inhibiting herbicide diuron on several types of symbiotic algae (diatom, dinoflagellate or rhodophyte) of benthic foraminifera in hospite. Diuron was shown to evoke a direct effect on photosynthetic efficiency (reduced effective PSII quantum yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 76 publications
(93 reference statements)
2
30
0
Order By: Relevance
“…In an experiment increasing nutrient levels and elevating pCO 2 , photosymbiont concentration in M. rossi was reduced more under the combined stress than when individual stressors acted in isolation (Reymond et al 2013). van Dam et al (2012) showed that populations of Foraminifera exposed to the herbicide Diuron become disproportionately more sensitive to temperature and both factors acted additively on the foraminiferal photosynthetic response. Ecotoxicological studies on the interaction of climate change with additional stressors, such as pesticide exposure, indicate a prevalence of synergistic interactions across different organisms (Holmstrup et al 2010;Kohler and Triebskorn 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an experiment increasing nutrient levels and elevating pCO 2 , photosymbiont concentration in M. rossi was reduced more under the combined stress than when individual stressors acted in isolation (Reymond et al 2013). van Dam et al (2012) showed that populations of Foraminifera exposed to the herbicide Diuron become disproportionately more sensitive to temperature and both factors acted additively on the foraminiferal photosynthetic response. Ecotoxicological studies on the interaction of climate change with additional stressors, such as pesticide exposure, indicate a prevalence of synergistic interactions across different organisms (Holmstrup et al 2010;Kohler and Triebskorn 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated temperatures and eutrophication can also have interactive negative effects on growth and survivorship in Marginopora vertebralis . Negative effects of elevated temperatures are more severe in the presence of low concentrations of the herbicide Diuron (van Dam et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This has application in plant growth models that build predictions based on multiple environmental conditions, and for the interpretation of routine seagrass health monitoring where both temperature and diuron exposure are known. Previously the effects of diuron and thermal stress has been shown to cause additive effects on in symbiotic corals41 and their isolated symbionts71 and in foraminifera55. Although outcomes for PSII activity in seagrass was also worse for combinations of temperature stress and herbicide exposure, the sub-additivity reported here may reflect a greater flexibility in PSII function across a wider thermal range as seagrasses are generally considered far more tolerant of thermal stress than corals and foraminifera72.…”
Section: Discussionmentioning
confidence: 54%
“…As a result, sub-optimal temperatures (both low and high) may cause reduced binding efficiency of diuron and thus change sensitivity to PSII herbicides, explaining the reduced IC 50 s at 20 °C and 40 °C. From another perspective, the presence of diuron (or other PSII herbicides) is likely to narrow the optimal temperature range for seagrass, resulting in stress responses at lower maximum temperatures, as reported for corals and foraminifera545571. Throughout the GBR lagoon and catchment area seasonally high sea surface temperatures coincide with the monsoonal flood plume events and the highest herbicide concentrations are detected near seagrass habitats under these conditions33.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation